Profile of people with pressure injuries admitted to the intensive care unit - Dos Santos Barreto, Renata Michelle; Lopes do Nascimento Santos, Renata; Viana Bezerra de Melo, Edluza Maria (O Mundo da Saúde, 2019)
Pressure Injury (PI) are lesions located on the skin and/or underlying tissue, usually over a bony prominence, or related to healthcare devices. They are considered a serious health problem in the hospital environment, representing a constant challenge for patients, professionals and institutions, due to the high incidence and prevalence in certain populations and the consequences resulting in increased morbidity and mortality. This study aimed to identify the profile of people with pressure injuries admitted to the intensive care units of a teaching hospital in Recife, PE. This is a descriptive study with a quantitative approach, with secondary data obtained from the records of the Dressing Committee of the Recife, PE school hospital. The collection took place from March to September 2015. 83 patients were identified with PI, predominantly >80 years old (26.5%), male (53.0%), the most frequently visited intensive care unit was the Clinic at 49.40%. As for mobility, 96.39% were bedridden, the anatomical location was often in the sacral region (80.72%), most had one lesion (87.95%) and they were mainly in stage 1 (53.01%). The most commonly used preventive measures were essential fatty acids (26.51%) and barrier creams (24.10%). With this study it is possible to focus on the elaboration and implementation of strategies for preventive measures in critical patient care, low cost and daily care.